Effects of caffeine intake and exercise intensity on executive and arousal vigilance - Sanchis, Carlos (2020)
During physical efforts and sport practice, vigilance is responsible for maintaining an optimal state of activation, guaranteeing the ability to quickly respond and detect unexpected, but critical, stimuli over time. Caffeine and physical exercise are able to modulate the activation state, affecting vigilance performance. The aim of the present work was to assess the specific effects and modulations of caffeine intake and two physical intensities on vigilance components. Participants performed an attentional task (ANTI-Vea) to measure the executive and arousal components of vigilance, in six double-blinded counterbalanced sessions combining caffeine, placebo, or no-ingestion, with light vs. moderate cyclergometer exercise. Exercise at moderate intensity improved executive vigilance with faster overall reaction time (RT), without impairing error rates. Instead, caffeine intake generally improved arousal vigilance. In conclusion, caffeine and acute exercise seems to moderate executive and arousal vigilance in different ways.